Transferência de alunos com deficiência intelectual das escolas especiais às escolas comuns sob diferentes perspectivas - Maturana, Ana Paula Pacheco Moraes (2016)
In the Brazilian educational contexto, the legislation guarantees the right to education of students target of Special Education (STSE) in common classes of regular schools. The enrollment of these students in public schools have grown year by year and this has imposed challenges for schools and teachers. In the case of students with ID, representing the largest contingent of STSE students, the previous tradition to the school inclusion policy, which was schooling in specialized institution, now divides the scene with the proposed new school in regular school. It is that educational policy has increasingly tried to make compulsory registration of all students of STSE in regular schools, although in the case of students with ID, this measure has bogged down in historical tradition placement in specialized institution. The result has been the increase in the flow of transfer students from specialized institutions for common schools, and vice versa, when the inclusion process is not successful. This study is proposed to investigate these processes of transfer of students from specialized institutions to mainstream schools and vice versa, considering the different perspectives of all those involved in the student with ID enrollment process. The general objectives of this study were to identify, describe and analyze possible factors that interfere with the transfer of students from special school to the regular or vice versa, in the conceptions of different actors. This is a descriptive research with a multiple case design. The study design involved the study of cases of students with ID were transferred from special schools to regular schools and vice versa. Five cases were analyzed: Saulo, Flavia, Fabio, Sofia and Fabiola. The research included 21 participants: five students, six family members and / or guardians and ten school personnel, including teachers, pedagogical coordinator, directors and teaching supervisor. Family members and school professionals answered a semi-structured interview. With students was applied the instrument procedure D-E. Analysis of the interviews identified: (1) the difficulty of adapting to the transition between schools, due to the lack of school supports, a previous preparation with students, parents and teachers and the late referral of students; (2) difficulties in the familyschool relationship eventually bring obstacles to the transfer and education of students; (3) expectations regarding the behavior and student learning with ID revealing an overvaluation of cognitive skills and (4) the assumptions of the participants on inclusion and its influence on practice with the student with ID. Regarding the participation of students, the established lines of analysis were aspects assigned by students of the special school and aspects assigned by students to the regular school. Students assigned to the special school the role of host and care and to the common school a place of learning and knowledge. The results confirm the authors presented in the literature review on the implementation of special education in inclusive environments, signaling that the views of teachers, managers and family against the inclusion will depend on the severity of the student's disability, skills and attitudes of professionals and It can only be seen by comparison of all the actors who are part of the process. The analysis of the results shows that the study achieved its goals and brought practical implications, political and scientific related to education of students with ID.